Reform of Mahar Law: An Analysis of the Pre-Islamic Shigar Marriage Tradition - diaana, riskaa; Riduan, Muhammad; Kamil, Muhammad Ihsanul; Jaidi, Muhammad (Jurnal Marital: Kajian Hukum Keluarga Islam, 2025)
Abstract : In the marriage practices of pre-Islamic Arab (Jahiliyah) society, which were rife with injustice, particularly in nikah shigar a form of exchange marriage where the dowry was not a gift from the groom to the bride but rather a compensation involving the exchange of the bride’s sister to the groom’s brother this practice reduced women to mere objects of family transactions, disregarding their dignity and autonomy. The purpose of this study is to analyze the influence of Jahiliyah marriage traditions, particularly nikah shigar, on the reform of Islamic family law, with a focus on the transformation of the dowry concept from a form of compensation to a mandatory right and a symbol of spiritual-emotional commitment. The method used is qualitative with a historical-normative approach, relying on a literature review of primary sources (the Qur’an, Hadith, and historical texts) and secondary sources (books, journals, and academic works). The analysis is conducted critically to identify continuities and discontinuities between pre-Islamic traditions and Islamic law. The main findings indicate that Islam introduced revolutionary reforms by completely abolishing practices like nikah shigar and similar customs. The dowry was reformed into iwadl, a mandatory financial and symbolic gift from the husband to the wife, affirming women’s economic and legal independence. Consequently, women were no longer treated as objects of exchange but as sovereign legal subjects. Marriage shifted from a transactional family arrangement to a bond based on mawaddah wa rahmah (love and compassion). This dowry reform serves as strong evidence that pre-Islamic traditions acted as a catalyst for fundamental changes in the Islamic family law system, while also affirming the principle of gender justice at the core of Islamic teachings. Abstrak : Dalam praktik pernikahan masyarakat Arab Pra-Islam (Jahiliyah) yang sarat ketidakadilan, khususnya nikah shigar, sebuah bentuk pernikahan tukar-menukar di mana mahar bukanlah pemberian dari mempelai pria kepada wanita, melainkan kompensasi berupa penyerahan saudara perempuan mempelai wanita kepada saudara mempelai pria. Praktik ini mereduksi perempuan menjadi objek transaksi keluarga, mengabaikan martabat dan otonomi mereka. Tujuan penelitian ini adalah menganalisis pengaruh tradisi pernikahan Jahiliyah, khususnya nikah shigar, terhadap reformasi hukum keluarga dalam Islam, dengan fokus pada transformasi konsep mahar dari bentuk kompensasi menjadi hak wajib dan simbol komitmen spiritual-emosional. Metode yang digunakan adalah kualitatif dengan pendekatan historis-normatif, mengandalkan studi literatur terhadap sumber primer (Al-Qur’an, Hadis, dan kitab sejarah) serta sekunder (buku, jurnal, dan karya akademik). Analisis dilakukan secara kritis untuk mengidentifikasi kontinuitas dan diskontinuitas antara tradisi pra-Islam dan hukum Islam. Temuan utama menunjukkan bahwa Islam melakukan reformasi revolusioner dengan menghapus habis praktik nikah shigar dan sejenisnya. Mahar direformasi menjadi “iwadl” pemberian wajib finansial dan simbolis dari suami kepada istri, yang menegaskan kemandirian ekonomi dan hukum perempuan. Dengan demikian, perempuan tidak lagi diperlakukan sebagai barang tukar, melainkan sebagai subjek hukum yang berdaulat. Pernikahan pun bergeser dari ikatan transaksional keluarga menjadi ikatan berbasis mawaddah wa rahmah (cinta dan kasih sayang). Reformasi mahar ini menjadi bukti kuat bahwa tradisi pra-Islam justru menjadi katalisator bagi perubahan mendasar dalam sistem hukum keluarga Islam, sekaligus menegaskan prinsip keadilan gender yang menjadi inti ajaran Islam.